Factors influencing the personal interest, and behavioural intention to become an accountant in Malaysia - Muhamad, Haslinah; Ong, Tze San; Katan, Maheran; Soh, Wei Ni (Human Resource Management Academic Research Society, 2020)
Based on low-interest figures among accounting graduates toward the accounting profession, this study tries to identify the factors that influence an accounting student’s career choice decision making in Malaysian public universities. By using the Social Cognitive Career Theory (SCCT) and Theory of Reasoned Action (TRA), this research tried to examine the influence of self-efficacy beliefs (technical and soft skills), perception about the accounting profession (image of accounting profession) and social behaviour to personal interest, consequently affect the behavioural intention to become an accountant. This research utilized an online Google survey with a total of 243 useable responses collected from undergraduate accounting students studying in Public Universities. IBM SPSS statistic version 22 and WarpPLS version 6 have been used to run the multi regression test. All hypotheses, except H1 and H3, were supported. It can be concluded that students’ soft skill selfefficacy and social influence have a positive effect on personal interest in pursuing accounting as a major. Social influence and personal interest also have a positive effect on behavioral intentions on pursuing accounting as a major. The findings of this study convey practical implications to the effective recruitment of the accounting profession in order to secure the supply of qualified professional accountants. Accounting educators can play their role as an influence agent to promote the profession, enhance self-efficacy belief and personal interest.